The problem of linguistic persona in linguistics and its place in the scientific system - Rapisheva, Zh.D.; Tuite, E.E.; Uazhanova, Z.N.; Karmanova, S.B. (KSU Publ., 2018)
The article deals with the state of the theory of the linguistic personality in linguistics, which causes an increased interest of modern scientists linguists. Such key questions of studying the linguistic personality are raised, such as the choice of the original term and the generic component, the establishment of the level of abstraction and structure definition. The relevant aspects of contemporary linguistics of the theory of the language personality that originated in the anthropocentric direction can be covered, which can be considered as collective and / or individual. And also the authors of the article prove that the prospects for the development of the theory of the linguistic personality are related to the cognitive, lingual-cultural and communicative directions of research.
Тіл біліміндегі тілдік тұлға мəселесі жəне оның ғылыми жүйедегі орны
Проблема языковой личности в лингвистике и ее место в научной системе
Keywords: linguistic persona; theory of linguistic persona; scientific paradigm; linguistics; personality; verbal-semantic level; cognitive (or the thesaurus) level; pragmatic level; language image of the universe